PERMASALAHAN SOSIAL PADA NOVEL PUDARNYA PESONA CLEOPATRA KARYA HABIBURRAHMAN EL SHIRAZY (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This is a reserach abaout social problem in novel Pudarnya Pesona Cleopatra written by Habiburrahman El Shirazy. The social problems in Pudarnya Pesona Cleopatra can be viewed economic aspect, culture aspect, environment and individual aspect. This research usus qualitatif approachment and using qulitatif descriptife method in the means to describe the social problems in novel of Pudarnya Pesona Cleopatra by Habiburrahman El Shirazy. The data’s sources of this research come from teks that is collected from novel Pudarnya Pesona Cleopatra. The data are collected by data collecting technic, then are grouped based on data analysis, there are 4 aspects, there are, 1. Economic (poverty,unemployment,criminals) 2. Culture (family’s problem. wars, birocracy, pollution)3. Environment (norm violation, population problem, enironmental problem, conflict, social gap 4. Individual (youth problemin modern society, sexuality, drugs addiction, mental problem, juvenile delinquency, intercommunication violence)Keywords: social problem, novel, habiburrahman El Shirazy, Pudarnya Pesona Cleopatra